English for Biomedical Science in Higher Education Studies: teacher's book - Chrimes, J. John (English for specific academic purposes/series ed.: Terry Phillips, 2015)
English for Biomedical Science is a skills-based course designed specifically for students of biomedical science who are about to enter English-medium tertiary level studies. It provides carefully graded practice and progressions in the key academic skills that all students need, such as listening to lectures and speaking in seminars. It also equips students with the specialist language they need to participate successfully within an biomedical science department. Extensive listening exercises come from biomedical science lectures, and all reading texts are taken from the same field of study. There is also a focus throughout on the key biomedical science vocabulary that students will need.